DETERMINATION OF SOME BIOCHEMICALS, PHYTOCHEMICALS AND ANTIOXIDANT PROPERTIES OF DIFFERENT PARTS OF Cichorium intybus L.: A COMPARATIVE STUDY - M. A. Shad; H. Nawaz; T. Rehman; N. Ikram (Journal of Animal and Plant Sciences, 2013)
The biochemical, phytochemical and antioxidant composition of root, stem, leaves and seeds of Cichorium intybus L was determined. A statistically significant difference (p>0.05) was observed among different parts of Cichorium intybus regarding the biochemical, phytochemical and antioxidant composition. The leaves were found to possess comparatively higher values of total sugars non-reducing sugars water soluble proteins total flavonoids, total phenolic acids and total antioxidants. On the other hand, seeds were found to possess comparatively higher contents of reducing sugars, salt soluble proteins and saponins. The phytochemical screening confirmed the presence of tannins, saponins, flavonoids, terpenoids, cardiac glycosides and anthocyanins in each part of the plant. The antioxidant potential of methanolic extracts of different parts was evaluated in terms of 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity and reducing power. The leaf extract was found to show comparatively low value of IC50 for DPPH inhibition and high reducing power. Due to good biochemical, phytochemical and antioxidant composition, Cichorium intybus leaves would be valuable candidate in pharmaceutical formulations and play an important role in improving the human, livestock and poultry health by participating in the antioxidant defence system against endogenous free radicals.
Keywords: Antioxidant Composition; Biochemical Analysis; Cichorium intybus; Phytochmical Screening; DPPH